Skill gap perceived between employers and accounting graduates in Ethiopia - Mohammed Getahun; Deresse Mersha (Financial Studies, 2020)
In the last decade, many researchers have criticized university accounting education programs for focusing more on the teaching of technical accounting and not on emphasizing accounting skill development. The aim of this study is to identify the knowledge subjects, skills & attitude needed for a graduate accountant in respect of employee's perceptions and employer expectations. Data were obtained from 236 employees and 118 employers from various organizations using a survey are compared with the perceived needs of a sample of employees and employers in Ethiopia. The findings indicate that there is an agreement between the perceptions of both groups, some significant gap still exists. These skills, knowledge and attitudes are relevant to preparing the graduates for careers as professional accountant such as communication & language skills, financial accounting & financial reporting knowledge, and professional competence and due care were the most important for accountants in work place rate by both the employers and graduate's students. The results ofstudy provide better information for academics, Employers, and students graduated in accounting, in bridging the perceived skills gap between employers and graduates. Moreover, study suggest that academician, unemployment, and employers of graduate students' better understanding the importance of the skills required in the current market needs, and higher university institutions to improve their curriculum in promotion quality graduates.
Keywords: M4; 330; Professional Accountant; Employers; skills; Ethiopia